KATA BIJAK DALAM NOVEL ANAK SEMUA BANGSA KARYA PRAMOEDYA ANANTA TOER: KAJIAN SOSIOLINGUISTIK - Cahyani, Dewi Aisya (Universitas Madura, 2023)
The study of sociolinguistics is the study of language that is closely related to the situations and conditions of a society, where the relationship is supported by social sciences and theory (sociology) and language (linguistics). The purpose of this study is to analyze and describe the words or sentences in the novel “Children of All Nations” by Pramoedya Ananta Toer using sociolinguistic studies. The method used in this research is descriptive qualitative method. Provision of data is done by tracing the appropriate literature studies and conducting data analysis. Primary data was collected from data from a novel by Pramoedya Ananta Toer entitled